Effect of warm-up and precooling on pacing during a 15-km cycling time trial in the heat - Levels, K.; Teunissen, L. P. J.; de Haan, A.; de Koning, J. J.; van Os, B.; Daanen, H. M. (International Journal of Sports Physiology and Performance, 2013)
Purpose: The best way to apply precooling for endurance exercise in the heat is still unclear. The authors analyzed the effect of different preparation regimens on pacing during a 15-km cycling time trial in the heat. Methods: Ten male subjects completed four 15-km time trials (30°C), preceded by different preparation regimes: 10 min cycling (WARM-UP), 30 min scalp cooling of which 10 min was cycling (SC+WARM-UP), ice-slurry ingestion (ICE), and ice slurry ingestion + 30 min scalp cooling (SC+ICE). Results: No differences were observed in finish time and mean power output, although power output was lower for WARM-UP than for SC+ICE during km 13-14 (17 ± 16 and 19 ± 14 W, respectively) and for ICE during km 13 (16 ± 16 W). Rectal temperature at the start of the time trial was lower for both ICE conditions (~36.7°C) than both WARMUP conditions (~37.1°C) and remained lower during the first part of the trial. Skin temperature and thermal sensation were lower at the start for SC+ICE. Conclusions: The preparation regimen providing the lowest body-heat content and sensation of coolness at the start (SC+ICE) was most beneficial for pacing during the latter stages of the time trial, although overall performance did not differ.